Assessing adverse childhood experiences in young refugees: a systematic review of available questionnaires - Abdelhamid, Shaymaa; Kraaijenvanger, Eline J.; Fischer, Joachim E.; Steinisch, Maria (European child & adolescent psychiatry, 2024)
Today, various questionnaires are available to assess Adverse Childhood Experiences (ACEs) in children; however, it is uncertain if these questionnaires are comprehensive in addressing adversities of vulnerable subgroups, specifically refugee children. This review’s objectives are to (1) identify current ACE questionnaires and determine if they are suitable in assessing refugee children’s adversities, and (2) identify those previously used within a refugee population. A systematic literature search was conducted across five databases for articles published since 2010, including studies using an ACE-questionnaire that recognized multiple adversities in healthy children and were published in English. A total of 103 ACE questionnaires were identified in 506 studies. Only 14 of the 103 questionnaires addressed a refugee-specific adversity. Their ability to capture refugee children’s experiences was limited: available questionnaires used a maximum of three items to assess refugee-specific adversities, covering only a fraction of forms of adversities relevant to refugee children. Psychometric characteristics were rarely reported. In addition, only two ACE questionnaires were used within a refugee population. With the tools currently available, it is not possible to comprehensively assess the exposure to and severity of the adversities faced by refugee children. The perpetuation of ongoing crises necessitates assessing refugee children’s adversities to understand how their wellbeing is affected and to identify children at risk.